Software project management (A pratical approach) - Chopra, Er. Rajiv; Chopra, Er, Rajiv (New Delhi, India : S.K. Kataria & Sons)
Many books on Software Project Management are available in the market but they tend to be dry and formal. I have made this book the most lucid and simplified so that a student feels as if a teacher is sitting behind him and guiding him. It can be used as a textbook for all graduates and postgraduates programs of UPTU, DU, GGSIPU, JNU, JNTU, MDU, GNDU, VTU, SRM and many more universities of India.
1. Introduction and software project planning -- 2. Project organization, scheduling and management issues -- 3. Project monitoring and control -- 4. Technical communication -- 5. Software quality assurance (SQA) and testing -- 6. Project management and project management tools -- Appendices -- Previous years examination papers -- Index.
Includes index.
Keywords: SOFTWARE PROJECT MANAGEMENT